Recoding of the stop codon UGA to glycine by a BD1-5/SN-2 bacterium and niche partitioning between Alpha- and Gammaproteobacteria in a tidal sediment microbial community naturally selected in a laboratory chemostat - Hanke, Anna; Hamann, Emmo; Sharma, Ritin; Geelhoed, Jeanine S.; Hargesheimer, Theresa; Kraft, Beate; Meyer, Volker; Lenk, Sabine; Osmers, Harald; Wu, Rong; Makinwa, Kofi; Hettich, Robert L.; et al. (Frontiers in Microbiology, 2014)
Sandy coastal sediments are global hotspots for microbial mineralization of organic matter and denitrification. These sediments are characterized by advective porewater flow, tidal cycling and an active and complex microbial community. Metagenomic sequencing of microbial communities sampled from such sediments showed that potential sulfur oxidizing Gammaproteobacteria and members of the enigmatic BD1-5/SN-2 candidate phylum were abundant in situ (>10% and ~2% respectively). By mimicking the dynamic oxic/anoxic environmental conditions of the sediment in a laboratory chemostat, a simplified microbial community was selected from the more complex inoculum. Metagenomics, proteomics and fluorescence in situ hybridization showed that this simplified community contained both a potential sulfur oxidizing Gammaproteobacterium (at 24±2% abundance) and a member of the BD1-5/SN-2 candidate phylum (at 7±6% abundance). Despite the abundant supply of organic substrates to the chemostat, proteomic analysis suggested that the selected gammaproteobacterium grew partially autotrophically and performed hydrogen/formate oxidation. The enrichment of a member of the BD1-5/SN-2 candidate phylum enabled, for the first time, direct microscopic observation by fluorescent in situ hybridization and the experimental validation of the previously predicted translation of the stop codon UGA into glycine.